Cut-off point for the trail making test to predict unsafe driving after stroke - Choi, Seong Youl (J Phys Ther Sci, 2016)
[Purpose] This study examined the cut-off point of the Trail Making Test in predicting the risk of unsafe driving in stroke patients. [Subjects and Methods] A total of 81 stroke patients with a driver’s license participated in this study. The DriveABLE Cognitive Assessment Tool, Trail Making Test-A, and Trail Making Test-B evaluations were conducted in all participants. All participants were classified into the safety or risk groups based on the DriveABLE Cognitive Assessment Tool evaluation results. The Trail Making Test results underwent a receiver operating characteristic analysis in each group. [Results] The results of the receiver operating characteristic curve analysis showed that the cut-off point for Trail Making Test-A was 32 seconds and the cut-off point for Trail Making Test-B was 79 seconds. The positive predictive values of the Trail Making Test-A and Trail Making Test-B were 98.3% and 98.3%, respectively, and the negative predictive values of the Trail Making Test-A and Trail Making Test-B were 81.0% and 73.9%, respectively. [Conclusion] The Trail Making Test is a useful tool for predicting the risk of unsafe driving in stroke patients. This tool is expected to be used more actively for screening stroke drivers with respect to their cognitive function.